2015
DOI: 10.3109/15368378.2015.1036070
|View full text |Cite
|
Sign up to set email alerts
|

Nanoassociate formation in highly diluted water solutions of potassium phenosan with and without permalloy shielding

Abstract: Diluted water solutions of anti-oxidant potassium phenosan, kept before explorations in "usual" conditions and in conditions of "permalloy container", i.e. shielding of solution from the influence of external low-frequency electromagnetic and/or geomagnetic fields, were studied. It is shown that in solutions kept in shielded conditions in the area of high dilution with a concentration of solutions lower than "threshold", nanoobjects called "nanoassociates", are not formed, and anomalous physicochemical and bio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
22
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(27 citation statements)
references
References 22 publications
2
22
0
Order By: Relevance
“…First, the homeopathic potency is capable of self-organizing and inducing formation of self-similar nano-structures in surrounding water. 5,8,[20][21][22][23][24][25][26][27] Second, multiple studies of plants have shown that homeopathic potencies induce formation of self-organized, unique poly-crystalline structures in the exudates of treated plant seedlings versus controls. 6,7,28,29 In other words, homeopathically prepared medicines may induce formation of self-similar crystalline nano-structures in water and/or in biological fluids within a living system.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…First, the homeopathic potency is capable of self-organizing and inducing formation of self-similar nano-structures in surrounding water. 5,8,[20][21][22][23][24][25][26][27] Second, multiple studies of plants have shown that homeopathic potencies induce formation of self-organized, unique poly-crystalline structures in the exudates of treated plant seedlings versus controls. 6,7,28,29 In other words, homeopathically prepared medicines may induce formation of self-similar crystalline nano-structures in water and/or in biological fluids within a living system.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
“…75 In parallel, Elia's laboratory previously demonstrated that pH changes induce measurable heat release and alterations in electrical conductance of homeopathically prepared medicine solutions. 8 Furthermore, multiple research groups have reported evidence that homeopathic manufacturing induces persistent formation of electromagnetic signal-induced, self-organized crystalline water nano-structures, termed "dissipative structures" by Elia et al, 8,76,77 "nano-associates" by Konovalov et al, 20,21 or "nano-pearls" (poly-crystals formed of many microscopic crystallites) by Meessen. 5 Crystalline structures at the nano-scale (or larger) spontaneously self-organize from an interaction of their constituent parts with each other and with their environment.…”
Section: Homeopathic Medicines As Complex Systemsmentioning
confidence: 99%
“…At the same time, the influence of materials of chips and communications on charge generation that are not in contact with the solution on the generation of charge in the solution flowing through the injector of the AFM-based fishing system is virtually not discussed in the literature. Also, it is known that the presence of macromolecules at low concentrations (including femtomolar ones) can influence the physicochemical properties of water (particularly, electrical conductivity, pH, surface tension, [13,14]. In the literature, it is discussed that these effects can be connected with the transitions between ortho-and para-states of water owing to pumping of mixed quantum states of ortho-/para-H 2 O with natural and anthropogenic electromagnetic radiation (at which analytical biochemical measurements are usually carried out) [15].…”
Section: Introductionmentioning
confidence: 99%
“…For example, the study of dilute solutions of potassium phenozane antioxidant (PP) by the DSC method showed that the PP solutions used in the range of formation of domains and nanoassociates [2,3] change the thermostability of the protein fraction of plasma membranes in the opposite direction -in the domain formation range, it increases, and in the nanoassociation formation region it is reduced. [27] Both domains and nanoassociates, starting at t>55 °C, are destroyed, the maximum deviations from additivity are observed in both cases in the 50-60 °C interval.…”
Section: S Ryzhkina Et Almentioning
confidence: 99%
“…[1][2][3] As a result of a comparative study of self-organization and properties of a diverse series of biologically active substances' solutions, prepared using the method of successive decimal dilution and exposed both to natural conditions (being kept on the laboratory bench) and to the full absence of external low-frequency electromagnetic fields (EMF) (being kept in a permalloy container), it has been shown that the diluted solutions of many biologically active substances (BAS) are in fact the disperse systems, where the role of the disperse phase is played by supramolecular ensembles of different nature -at first these are the small substance aggregates and supramolecular domains, while with dilution below the threshold concentration (C th ) they reorganize into nanoassociates of hundreds of nm in size. It is shown that it is this kind of reorganization that is responsible for the nonmonotonic concentration dependencies of the systems' physicochemical properties, and not the decrease in the initial substance's concentration.…”
Section: Introductionmentioning
confidence: 99%